Kajian Literatur Strategi Pembelajaran untuk Mengatasi Kesulitan Mahasiswa pada Kapita Selekta Matematika Sekolah Menengah - Mariatul Kiftia Shakila; Nur Hasanah Siregar (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
The Selected Topics in Secondary School Mathematics course is a strategic subject in the mathematics education program, as it plays a crucial role in connecting mathematical theory with its application in secondary school teaching. However, various studies indicate that students often face difficulties in understanding this subject, particularly in mastering fundamental concepts, maintaining learning motivation, and applying concepts in instructional contexts. This study aims to identify effective learning strategies to overcome these challenges through a literature review approach. Data were collected from national and international journals published within the last five years, focusing on learning strategies and students’ learning difficulties. The findings reveal that the implementation of Project-Based Learning can enhance conceptual understanding and higher-order thinking skills, metacognitive-based strategies promote independent learning, the integration of character values strengthens motivation and academic ethics, and the use of interactive digital media facilitates the visualization of abstract concepts. This review concludes that the development of holistic, adaptive, and contextual learning strategies serves as an effective solution to address students’ difficulties in the Selected Topics in Secondary School Mathematics course while preparing them to become competent and character-driven future educators.